L’architecture et le paysage du village berbère de Zraoua dans les montagnes du sud-est de la Tunisie : le patrimoine dans un lieu en voie d’abandon - Miguel Reimão Costa; Nouri Boukhchim; Desidério Batista; Meriem Marzouki (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
The Architecture and Landscape of the Berber Village of Zraoua, in the Mountains of South-Eastern Tunisia: Heritage of a Place in AbandonmentThe village of Zraoua, in southern Tunisia, is one of the villages of the Jebel Dahar whose population underwent a process of programmed displacement in the third quarter of the 20th century. This abandoned village constitutes an interesting case for the integrated study of vernacular architecture and cultural landscapes in Mediterranean mountainous regions. Biophysical dimensions and social structures reveal themselves as essential factors for interpreting the diversity and specificity of courtyard houses in this region (intra-wall house, semi-troglodyte house, ridge house and hillside house); for reconstituting the different phases of the urban evolution; and for understanding a landscape construction system which is very adapted to the territory’s resource scarcity (terraces on the thalweg lines, draining surfaces on the slopes and abundant presence of cisterns).